RI 4703 Investigation Of New Galena Lead Deposit Bucks County, Pa. - Kenneth M. Earl (The National Institute for Occupational Safety and Health (NIOSH), 1950)
In its investigation of deposits of strategic minerals, the Bureau of Mines did some development drilling at the New Galena Deposit in an endeavor to find an additional source of supply of lead. In Bucks County, lead and zinc minerals have been found in shales over a largo area west and northwest of Doylestown. Considerable mining has been done in the vicinity of New Galena on the North Branch of Noshaminy Creek, 3 miles northwest of Doylestown. It has not been possible to obtain a satisfactory history of the New Galena mine, as there is much disagreement in statements. Most of the mining was done in open pits. Two shafts were sunk to shallow depth; one of these became part of the main pit' which is 256 foot long, 50 to 75 feet wide, and 20 to 44 feet deep. Small pits 8 to 10 foot square wore sunk on the ore zone, which extends some 1450 feet to the southwest. The rock containing the minerals is either black or gray shale. The gray material closely resembles limestone. The following minerals have been reported from the mine: quartz, ankerite, calcite, galena, sphalerite, pyrite, chalcopyrite, and bornite. Some of the galena has yielded 10 to 15 ounces of silver and 10 cents in gold per ton. The average grade of the ore as mined is not known. To investigate the downward extension of the ore shoot, the Bureau drilled two holes aggregating 373.9 feet, No additional ore was developed by this work.